Ligand-enabled gold-catalyzed C(sp(2))-n cross-coupling reactions of aryl iodides with amines - Akram, Manjur O.; Das, Avishek; Chakrabarty, Indradweep; Patil, Nitin T. (Organic Letters, 2019)
The first example of ancillary (P,N)-ligand-enabled gold-catalyzed C-N cross-coupling reactions of aryl iodides with amines is reported. The high generality of the reaction in de novo synthesis, late-stage modifications, and cascade processes to access functionalized indolinones and carbazoles underscores the synthetic potential of the presented strategy. Monitoring the reaction with ESI-HRMS and NMR provided strong evidence for the in situ formation of putative high valent Au(III) intermediates.